2021
DOI: 10.1080/23802359.2021.1934160
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Machilus robusta W. W. Smith (Lauraceae) from Jiangxi Province, China

Abstract: Machilus robusta W. W. Smith is an evergreen plant distributed in the Yangtze River Basin and the south regions of China. Here we analyzed the complete chloroplast (cp) genome sequence of M. robusta to determine its structure and evolutionary relationship to other Lauraceae. The cp genome is 152,737 bp in length and has an overall GC content of 39.2% The genome includes a large single-copy (LSC) region of 93,706 bp and a small single-copy (SSC) region of 18,885 bp, and these are separated by a pair of inverted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…The results here showed that all Lauraceae species could be divided into two broad groups, genera Machilus , Neocinnamomum , and Cassytha clustered into one group; Cryptocarya , Endiandra , and Beilschmiedia clustered into another. The phylogenetic relationship of the Machilus genera obtained in this study was consistent with the results obtained by Wu et al [ 45 ]. The results of this study will contribute to the subsequent phylogenetic studies and species identification of Machilus genera.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results here showed that all Lauraceae species could be divided into two broad groups, genera Machilus , Neocinnamomum , and Cassytha clustered into one group; Cryptocarya , Endiandra , and Beilschmiedia clustered into another. The phylogenetic relationship of the Machilus genera obtained in this study was consistent with the results obtained by Wu et al [ 45 ]. The results of this study will contribute to the subsequent phylogenetic studies and species identification of Machilus genera.…”
Section: Discussionsupporting
confidence: 92%
“…The published lengths of the cp genomes of the genus Machilus ranged from 152,621 to 153,943 bp [ 19 , 45 , 46 ]. In comparison, the total length of the whole cp sequence of M. chuanchienensis assembled in this study was 152,748 bp, indicating that its cp genome size was in line with the traits of the Machilus species.…”
Section: Discussionmentioning
confidence: 99%